Experimental study of Pinus densiflora Siebold et Zuccarini on Hyperlipidemia and lipid in Rats - Kim, Dae-Hyun; Soh, Kyung-Sun (Korean Pharmacopuncture Institute, 2007)
In order to study the effects of Pinus densiflora on hyperlipidemia and lipid in rats, we divided the rats into groups(Normal group, Control group and Sample group) and perfomed the experimental research. Hyperlipidemia and lipid in rats were induced by high fat diets for 8weeks. The sample group was administerd the extract of Pinus densiflora for 14 days and control group was administerd equal dose of oral. And then we measured the amount of serum triglyceride, Total cholesterol, LDL-cholesterol, HDL-cholesterol, Free Fatty Acid, phospholipid, Insuline, Laptin, Body weight, epididymis fat weight & rate, epididymis fat cell, Cardiac Risk Factor(CRF). The results were as followers : 1. Sample Group showed decreasing effects on Total cholesterol, Trigylceride, LDL-cholesterol, and Phospholipid levels in serum and CRF significantly. 2. Sample Group showed increasing effects on HDL-cholesterol level in serum significantly. 3. Sample Group showed decreasing effects on Insuline in serum significantly. 4. Sample Group showed increasing effects on Laptin in serum significantly. 5. Sample Group showed decreasing effects on Body weight, epididymis fat weight & rate, epididymis fat cell significantly. According to the above results, Pinus densiflora showed significant decreasing effects on hyperlipidemia and lipid in rats, it is considered that it is appropriate to apply for hyperlipidemia, obesity.